Kajian Kapasitas Masyarakat terhadap Bencana Kekeringan di Desa Windurojo Kabupaten Pekalongan - Fajar Adie Nugraha; Maryono Maryono (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Nugraha FA, Maryono M. 2020. Drought community capacity assessment in Windurojo village, Pekalongan regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Windurojo Village is an area in Pekalongan Regency which is quite often hit by drought. In terms of morphogenesis, Windurojo Village is located in folds of structural hills with soil types dominated by grumusol. This makes during the dry season, the wells in the village dry up faster than other areas. A village scale disaster capacity study needs to be carried out in these areas so that the results of the study are more specific and have a more direct impact on the community. So that the purpose of this study is to determine the level of capacity of village scale units in Windurojo Village, Kesesi District, Pekalongan Regency. The process of collecting data is observation and interviews which are processed quantitatively. The analysis technique used is scoring. The results of the village scale capacity analysis show that there is only one hamlet with a low capacity, namely Dusun Serang, while Dusun Leles has a high level of capacity, Dusun Karangmoncol and Dusun Kuthawangi have a moderate level of capacity. From the findings, we think that the drought in Serang Hamlet is a socio-economic drought.